Analisis Pengetahuan Masyarakat Tentang Zakat Produktif - Wulan, Wulan; Alparizi, Vikram; Divia Kasi, Tri; Arofatul Maula, Dina (CV. Publikasi Indonesia, 2023)
So far, productive zakat has not been fully understood correctly by the people of Indonesia, this is because there is not much understanding of productive zakat. This is due to the view of society, especially the Muzakki that zakat fitrah is the most important zakat. In Islam zakat is known as a way of empowering the people with management funds coming from people's funds, productive zakat was born due to the encouragement of the times where technology is moving forward so that the movement of collecting zakat is flexible and covers any space. Productive zakat and consumptive zakat have a big impact on the welfare of the people, but it needs to be emphasized that productive zakat has a greater value for the benefit of mustahik and has the potential to become productive zakat in society. Indonesian government agencies have worked through the efforts of BAZNAS (National Amil Zakat Agency) as amil Zakat and the role of zakat management is not only to support the poor or the needy, but also a non-temporary permanent goal that is the right step. alleviate poverty and can increase Assess the level of poverty by providing productive zakat assistance.